New Perspectives in Cardiac and Vascular Diseases - Pietro Scicchitano; Francesco Massari (Biomedicines, 2025)
Understanding the physiopathology of cardiac and vascular diseases presents a challenge to clinicians due to their intricate biochemical and molecular mechanisms [...]